How conservative are sexual pheromones? : a cross-genera study of Plethodontid salamanders - Love, Christopher Brannon (2013)
Pheromones play a pivotal role in salamander reproductive behavior. Males deliver internally made pheromones from their mental gland to females during courtship interactions in the family Plethodontidae. These courtship pheromones typically increase female receptivity to mating by lowering courtship time. Differences in pheromone structure are thought to contribute to mating isolation among species. This experiment tested whether Plethodon shermani pheromones stimulated mating in a plethodontid salamander of a different genus. Mating trials were conducted with gravid female and deglanded male pairs of Desmognathus ocoee, while delivering D. ocoee pheromone, P. shermani pheromone, or saline control. Results showed that pairs receiving P. shermani pheromone spent twice as much time in tail-straddle walk when compared to the saline control, and 1.6 as much time in tail-straddle walk compared to native D. ocoee pheromone. These results indicate that pheromones are possibly specific to a given species and are not used as general mating stimulus, thereby possibly acting as a reproductive isolating mechanism among plethodontid salamanders.